Passive and Antipassive in Sasak (e-Journal of Linguistics, 2020)
This paper deals with the constructions of passive andantipassive in Sasak Kuto-Kute dialect (SKD) related tovalency decrease. The study involved 70 verbs proposed byMalchukov and Comrie (2010) and applying the theory oftypology linguistics from Dixon (2012) for data analysis. Thefinding showed that passive in this dialect can appear inthree forms: the use of morphological marking (confix ke- -n), syntactic marking (preposition siq ‘by’) and no markingsat all. For the last form, the construction can only bedetected through the movements of the arguments with thecase being limited to A with singular pronouns (ku ‘I’, diq‘you’ and ia ‘s/he’), and first plural pronoun (kami ‘we’).The syntactic passive marker in SKD is very productive andmore common compared to the morphological marker. Asfor antipassive, in this dialect the construction was found tobe formed only through morphological markings, whichinvolved the use of nasal prefixes such as meny- and me- andconfix ng- -ang as the AP markers.
Keywords: Sasak; Passive; Antipassive; Valency decrease